Negative ion resonance measurements in the autoionizing region of helium measured across the complete angular scattering range (0°-180°) - Ward, R.; Cubric, D.; Bowring, N.; King, G; Read, F.; Fursa, Dmitry; Bray, Igor (IOP Publishing, 2013)
Excitation function measurements for the decay of the 2s22p 2P and 2s2p2 2D triply excited negative ion resonances in helium to singly excited n = 2 states have been measured. These excitation functions have been determined across the complete angular range (0–180°) using a magnetic angle changer with a soft-iron core. The convergent close-coupling method has been used to calculate the cross sections, with the underlying complexity of the problem not yet being able to be fully resolved. Agreement between the present experimental data and previous experimental data is good, with these excitation functions confirming the presence of an unusual (2s22p)2P resonance behaviour in the 21S channel at 90°, where this would not usually be expected. Resonance energy and width values have been obtained, with a mean energy for the (2s22p)2P resonance of 57.20 ± 0.08 eV and a mean width of 73 ± 20 meV, and a mean energy of the (2s2p2)2D resonance of 58.30 ± 0.08 eV and a mean width of 59 ± 27 meV. Resonant cross section and ρ2 values have been calculated across the angular range for the first time, providing angular distribution data on decay propensities for both resonances.